Insights into periodontal disease: comparative analysis of animal models - Barik, Binapani; Chawla, Saurabh; Satapathy, Bhabani Sankar; Pattanik, Swadesh Kumar; Kumar, J. Aravind; Al-Farraj, Saleh; Pattnaik, Gurudutta; Sillanpää, Mika (Frontiers in Dental Medicine, 2025)
Periodontal disease is a progressive condition characterized by the degradation of gingival tissues, periodontal ligaments, and alveolar bone, often resulting in tooth loss if untreated. Its pathogenesis is influenced by bacterial infections, host immune responses, and environmental factors. While human cell cultures provide insights into cellular mechanisms, animal models play a crucial role in understanding the complex host-pathogen interactions and developing therapeutic interventions. Various species, including rodents, dogs, non-human primates, and mini-pigs, have been employed in periodontal research due to their anatomical and immunological similarities to humans. These models allow the study of disease progression, systemic effects, and potential treatments in a controlled environment. However, challenges such as anatomical differences, ethical concerns, and the difficulty of accurately replicating human periodontal disease remain. Despite these limitations, animal models are indispensable for advancing periodontal research, offering insights into disease mechanisms and contributing to the development of novel therapies. This review evaluates the strengths and limitations of several animal models used in periodontal disease studies, emphasizing the need for further refinement to enhance their relevance to human conditions.